Visualising library locations with Mobile Augmented Reality (Lib-MAR) / Nurhidayah Hashim, Ahmad Nadzri Mohamad and Dr. Tengku Adil Tengku Izhar - Hashim, Nurhidayah; Mohamad, Ahmad Nadzri; Tengku Izhar, Tengku Adil (Research Management Institute (RMI), 2017)
Massive developments of computing application create an opportunity for library administrators to engage with users in an interactive manner. One of the emerging applications is the use of Mobile Augmented Reality (MAR). In essence, various studies reported cost and technical knowledge as a fundamental component in MAR success. However, free and low-cost MAR platforms were made available for navigational purposes but less demonstrated in the literature. Hence, the objective of this study was to demonstrate the use of Mobile Augmented Reality (MAR) and its processes involved in mapping of Tun Abdul Razak Libraries, Universiti Teknologi Mara (UiTM), Shah Alam, Malaysia. For this purpose, location-based MAR application was used and integrated with geographical data on Google Maps through Keyhole Markup Language (KML) file. Relevant data and locational information was also incorporated to aid visualisation of library locations through smartphone. As a result, a new AR world was created and named "PTAR Mobile Augmented Reality (Lib-MAR)". Library users can use this AR tool with their smartphone as a guide to library locations on university surroundings. Technique shown in this study is applicable for library administrators to engage and aid users in library navigation, improving accessibility and resources discovery.